2011
DOI: 10.1007/s10616-011-9343-z
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus gasseri OLL2809 inhibits development of ectopic endometrial cell in peritoneal cavity via activation of NK cells in a murine endometriosis model

Abstract: We have previously reported that peritoneal administration of interleukin-12 (IL-12) suppresses development of ectopic endometriotic lesions via activation of natural killer (NK) cells in a mouse endometriosis model. Lactobacillus gasseri OLL2809 is one of a probiotic lactobacillus that has been selected on an ability to stimulate production of IL-12 from murine splenocytes. In this study, we examined whether the oral administration of heatkilled L. gasseri OLL2809 suppressed development of endometriosis. Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Itoh et al conducted mouse model experiments and found that the oral administration of probiotics activates peritoneal NK cells, and reduces endometriotic lesion formation. 60 Further, an extract of the white mistletoe tree, Helixor A, also directly activates NK cell cytotoxicity. 56 By adapting a strategy for cancer immunotherapy, 61 Montenegro et al administered intraperitoneal injections of IL-2-activated NK cells and reduced lesion formation in a mouse endometriosis model.…”
Section: Activation Of Nk Cells: Potential For a New Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Itoh et al conducted mouse model experiments and found that the oral administration of probiotics activates peritoneal NK cells, and reduces endometriotic lesion formation. 60 Further, an extract of the white mistletoe tree, Helixor A, also directly activates NK cell cytotoxicity. 56 By adapting a strategy for cancer immunotherapy, 61 Montenegro et al administered intraperitoneal injections of IL-2-activated NK cells and reduced lesion formation in a mouse endometriosis model.…”
Section: Activation Of Nk Cells: Potential For a New Therapymentioning
confidence: 99%
“…Itoh et al . conducted mouse model experiments and found that the oral administration of probiotics activates peritoneal NK cells, and reduces endometriotic lesion formation . Further, an extract of the white mistletoe tree, Helixor A, also directly activates NK cell cytotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the preventive efficacy of OLL2809 on a mouse endometriosis model by activating NK cells. 5) We evaluated the effect of OLL2809 on existing endometriosis in rats. In addition, recently we reported that the estrus cycle affected the healing process in a rat implanted endometriosis model, and found that the autoimplanted endometriosis in the diestrus did not heal readily by sequential endoscopic observation.…”
Section: Discussionmentioning
confidence: 99%
“…We observed recently a suppressive effect of IL-12 on the development of ectopic endometrial lesions, and found that it was due to activation of NK cells. 5) OLL2809 is a probiotic Lactobacillus that was selected on the basis of its immune stimulatory activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation